Does price tolerance depend upon the type of product in e-retailing? Role of customer satisfaction, trust, loyalty, and perceived value. (17th August 2020) - Pandey, Neeraj; Tripathi, Avinash; Jain, Devendra; Roy, Saptrshi
ABSTRACT: With the vast amount of information available to online shoppers at a simple click of mouse and touch in smartphones, the price comparison has become a very easy task. However, it has also increased the difficulty of online retailers to attract and retain price-sensitive buyers. This research looks into factors that influence price tolerance of buyers while buying different categories of products online. This study uses the analytic hierarchy process to determine the weightages of all the influencing factors and then determine their relative importance for next-stage survey. This study found that impact of customer satisfaction, trust, loyalty, and perceived value on price tolerance varied according to the nature of products. These results show that the buyers are more price tolerant to foreign-owned e-retailers for buying electronic goods in comparison to Indian start-up e-retailers, probably because of belief in standards. The study has implications for the managers, as it finds that trust and loyalty are more important factors than customer satisfaction and perceived value for e-retailing. Also, the trust and satisfaction are quite significant factors for e-retailing electric items in comparison to nonelectric items.